1998
DOI: 10.1093/sleep/21.6.569
|View full text |Cite
|
Sign up to set email alerts
|

A CLOCK Polymorphism Associated with Human Diurnal Preference

Abstract: A single nucleotide polymorphism located in the 3' flanking region of the human CLOCK gene was investigated as a predictor of diurnal preference in a population-based random sample of 410 normal adults. Morningness-eveningness preferences were determined using the 19-item Home-Ostberg questionnaire. Subjects carrying one of the two CLOCK alleles, 3111C, had a significantly lower mean Horne-Ostberg score. The distribution of scores was clearly shifted toward eveningness for these subjects. The score difference … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
331
8
15

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 548 publications
(366 citation statements)
references
References 28 publications
12
331
8
15
Order By: Relevance
“…17 Although we did not perform any assessment of sleep patterns in our subjects, it is of interest that the rs1801260 polymorphism has previously been associated with sleep dysregulation in humans in many [31][32][33][34][35][36][37][38] but not all studies. 39 These findings, together with the present results may provide genetic evidence to support epidemiological studies associating sleep disturbance with the development of diabetes and obesity.…”
Section: Discussionmentioning
confidence: 99%
“…17 Although we did not perform any assessment of sleep patterns in our subjects, it is of interest that the rs1801260 polymorphism has previously been associated with sleep dysregulation in humans in many [31][32][33][34][35][36][37][38] but not all studies. 39 These findings, together with the present results may provide genetic evidence to support epidemiological studies associating sleep disturbance with the development of diabetes and obesity.…”
Section: Discussionmentioning
confidence: 99%
“…A subset of the material (82 patients and 82 controls) has also been investigated for other serotonin-related polymorphisms (Johansson et al, 2001), but because of the limited number of samples this was not corrected for here. The power calculation was performed as described elsewhere (Johansson et al, 2001), assuming a ¼ 0.01, b ¼ 0.20, and allele frequencies in the control group identical to a previously published study (Katzenberg et al, 1998), or, when there were no previous reports, the observed frequencies. The distribution of GSS or MES within groups under analysis sometimes deviated from the normal distribution (data not shown), and therefore both parametric (one-way ANOVA or unpaired t-test) and nonparametric (Kruskal-Wallis or Wilcoxon rank sum) test methods were used when appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…We have genotyped European SAD patients and healthy matched controls for four single nucleotide polymorphisms in genes related to intrinsic circadian oscillators; CLOCK 3111 C/T (Katzenberg et al, 1998), Period2 1244 Gly/Glu (NCBI dbSNP database (www.ncbi.nlm.nih.gov): rs934945), Period3 647 Val/Gly (Ebisawa et al, 2001), and NPAS2 471 Leu/Ser (Celera Human SNP Database (www.cds.celera. com): CV2153849).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even individuals that are genetically predisposed towards "eveningness" (a preference for the evening) versus "morningness" (a preference for the morning) are more likely to develop depression (Drennan et al, 1991;Chelminski et al, 1999). Genetic variations in the circadian genes have been found to associate with these sleep disorders and diurnal preference measures including an association between certain variants of Per2, and CK1δ with FASPS; Per3, CLOCK, and CK1ε with DSPS; and Per1, Per2, Per3 and CLOCK with diurnal preference (Katzenberg et al, 1998;Iwase et al, 2002;Archer et al, 2003;Johansson et al, 2003;Takano et al, 2004;Carpen et al, 2005;Mishima et al, 2005;Xu et al, 2005;Carpen et al, 2006;Vanselow et al, 2006). This suggests a connection between proper mood regulation and a normal functioning circadian clock.…”
Section: A Generally Disrupted Clockmentioning
confidence: 99%